Prejudice across America - Waller, James, 1961- (University Press of Mississippi, 2000)
The experiences of a teacher and his white students on a nationwide trek toward racial understanding. In 1998 James Waller took twenty-one white college students from Washington state on a month-long journey. Prejudice Across America is the record of their interaction with the American Indian, Asian American, African American, Hispanic, and Jewish experiences nationwide. Few books have so directly and humanly captured the moment when whites confront the realities of those living as a minority in America. Waller reports here on this innovative and award-winning trek. In Los Angeles, San Francis.